2020
DOI: 10.1111/jace.17365
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the control of electrophoretic process parameters to tune the ytterbium disilicate coatings microstructure

Abstract: Suspensions of ytterbium disilicate in isopropanol were prepared using iodine dispersant. Their zeta potential, electrical conductivity, and pH dependence with iodine concentration is detailed. Electrophoretic deposition was performed on silicon substrates at various voltages (100-200 V) and times (until 10 minutes) and the growth dynamic was investigated. It was observed that the deposited mass reaches a maximum value for [I 2 ] = 0.2 g/L, and the coating microstructure becomes porous at higher iodine concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although EPD has not been widely used for the processing of EBCs, preliminary works on the processing of rare-earth silicate EBC via EPD were undertaken by Prioux et al [55] and Yilmaz et al [56]. Prioux et al [55] studied the effect of dispersant concentration (iodine), applied voltage, and deposition time on microstructural characteristics of Yb 2-Si 2 O 7 green coatings such as thickness, density, and homogeneity. They reported that increasing dispersant concentration, up to 2 g/L, increased the deposition rates, but a further increase resulted in a reduction in the relative coating density.…”
Section: Electrophoretic Deposition (Epd)mentioning
confidence: 99%
“…Although EPD has not been widely used for the processing of EBCs, preliminary works on the processing of rare-earth silicate EBC via EPD were undertaken by Prioux et al [55] and Yilmaz et al [56]. Prioux et al [55] studied the effect of dispersant concentration (iodine), applied voltage, and deposition time on microstructural characteristics of Yb 2-Si 2 O 7 green coatings such as thickness, density, and homogeneity. They reported that increasing dispersant concentration, up to 2 g/L, increased the deposition rates, but a further increase resulted in a reduction in the relative coating density.…”
Section: Electrophoretic Deposition (Epd)mentioning
confidence: 99%
“…Ceramic particles find applications in protective coatings. These include so‐called thermal barrier coatings or environmental barrier coatings for engine applications, mostly in the aeronautics industry [7–9] . For these applications, particles size range is 0.02–2 μm.…”
Section: Introductionmentioning
confidence: 99%
“…These include so-called thermal barrier coatings or environmental barrier coatings for engine applications, mostly in the aeronautics industry. [7][8][9] For these applications, particles size range is 0.02-2 μm. In these fields, particles are deposited through electrophoretic deposition (EPD), allowing a quite dense and thin deposit to be obtained compared with more conventional ceramic deposition processes, for instance thermal spray deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the short life of cordieritemullite refractory materials, associated with destructive processes caused by aggressive factors in their surface layers [1], it is advisable to protect the surface of refractories by coating. The use of known coating compositions for the protection of cordierite-mullite refractories is unacceptable due to the significant difference between the thermal coefficients of linear expansion (TCLE) of these coatings and the substrate ((6-10)•10 -6 K -1 ) [2][3][4][5][6]. The coating for the protection of cordierite-mullite refractories should have a composition that will provide a TCLE value close to that of cordierite ceramics, i.e., within ((2.0-3.5)•10 -6 K -1 ).…”
Section: Introductionmentioning
confidence: 99%